Highly selective synthesis of multicarbon compounds by carbon dioxide hydrogenation over Pt nanocrystals anchoring Ru clusters. Issue 12 (20th May 2022) - Yu, Yulv; Cai, Yichen; Liang, Minghui; Tan, Xin; Huang, Jin; Kotegawa, Fukue; Li, Zezhou; Zhou, Jihan; Jiang, Hong; Harada, Masafumi; Wang, Yuan
Abstract : Carbon supported Pt nanocrystals anchoring small Ru nanoclusters (Ru- co -Pt/C) could catalyze CO2 hydrogenation to form multi-carbon compounds (C2 –C26 ) with an extraordinary C2+ selectivity of 90.1% at 130 °C. Abstract : Selective conversion of CO2 to multicarbon compounds at low temperatures is a promising and challenging way to synthesize valuable chemicals and energy carriers by consuming CO2 . However, C–C coupling possesses high energy barriers over usual catalysts, resulting in low selectivities for multicarbon compounds. Small Ru clusters anchored on Pt nanoclusters (Ru- co -Pt) on carbon were prepared for the first time in this work which could catalyze CO2 hydrogenation to form C1 –C22 compounds at 130 °C with a C2+ selectivity of 90.1%, much higher than the values ever reported. It was found that Ru- co -Pt exhibited a much lower energy barrier for CH2 + CH2 coupling compared to Ru or Pt nanoclusters, and those for CH2 or CH3 hydrogenation. This new knowledge well accounts for the obtained high C2+ selectivity and provides a realistic strategy for developing advanced catalysts for synthesizing multicarbon hydrocarbons and alcohols and decreasing methane formation in CO2 hydrogenation.